Seasonality of P wave microseisms from NCF-based beamforming using ChinArray. Issue 3 (15th March 2018) - Wang, Weitao; Gerstoft, Peter; Wang, Baoshan
Summary: Teleseismic P wave microseisms produce interference signals with high apparent velocity in noise cross-correlation functions (NCFs). Sources of P wave microseisms can be located with NCFs from seismic arrays. Using the vertical-vertical component NCFs from a large-aperture array in southwestern China (ChinArray), we studied the P wave source locations and their seasonality of microseisms at two period bands (8–12 and 4–8 s) with an NCF-based beamforming method. The sources of P, PP and PKPbc waves are located. The ambiguity between P and PP source locations is analysed using averaged significant ocean wave height and sea surface pressure as constraints. The results indicate that the persistent P wave sources are mainly located in the deep oceans such as the North Atlantic, North Pacific and Southern Ocean, in agreement with previous studies. The Gulf of Alaska is found to generate P waves favouring the 8–12 s period band. The seasonality of P wave sources is consistent with the hemispheric storm pattern, which is stronger in local winter. Using the identified sources, arrival times of the interference signals are predicted and agree well with observations. The interference signals exhibit seasonal variation, indicating that body wave microseisms in southwestern China are from multiple seasonal sources.